HuR binding to cytoplasmic mRNA is perturbed by heat shock - Gallouzi, Imed-Eddine (The National Academy of Sciences, 2000)
AU-rich elements (AREs) located in the 3′ untranslated region target the mRNAs encoding many protooncoproteins, cytokines, and lymphokines for rapid degradation. HuR, a ubiquitously expressed member of the embryonic lethal abnormal vision (ELAV) family of RNA-binding proteins, binds ARE sequences and selectively stabilizes ARE-containing reporter mRNAs when overexpressed in transiently transfected cells. HuR appears predominantly nucleoplasmic but has been shown to shuttle between the nucleus and cytoplasm via a novel shuttling sequence HNS. We report generation of a mouse monoclonal antibody 3A2 that both immunoblots and immunoprecipitates HuR protein; it recognizes an epitope located in the first of HuR's three RNA recognition motifs. This antibody was used to probe HuR interactions with mRNA before and after heat shock, a condition that has been reported to stabilize ARE-containing mRNAs. At 37°C, approximately one-third of the cytoplasmic HuR appears polysome associated, and in vivo UV crosslinking reveals that HuR interactions with poly(A)(+) RNA are predominantly cytoplasmic rather than nuclear. This comprises evidence that HuR directly interacts with mRNA in vivo. After heat shock, 12–15% of HuR accumulates in discrete foci in the cytoplasm, but surprisingly the majority of HuR crosslinks instead to nuclear poly(A)(+) RNA, whose levels are dramatically increased in the stressed cells. This behavior of HuR differs from that of another ARE-binding protein, hnRNP D, which has been implicated as an effector of mRNA decay rather than mRNA stabilization and of the general pre-RNA-binding protein hnRNP A1. We interpret these differences to mean that the temporal association of HuR with ARE-containing mRNAs is different from that of these other two proteins.